Palestinian Public Opinion Polls No. 35 - (:unkn) unknown (An-Najah National University/ Opinion Polls and Survey Studies Unit, 2008)
The Palestinian political realities are still suffering from a sate of division ‎between the West Bank ‎and the Gaza Strip and the division is intensified ‎by a verbal conflict that escalates with the ‎approaching end of President ‎Mahmoud Abbas's term. Several legal councilors and advisors assert ‎‎that the President's term ends simultaneously with the term of the PLC in ‎January 2010. Others, ‎however, say that the President's term ends in ‎January of 2009‎ On the other side of the Palestinian scene, Palestinian Israeli negotiations ‎are stand still; they do ‎not show any progress. More than one Palestinian ‎official declared that the negotiations are not ‎going to lead to the creation ‎of a Palestinian state by the end of this year as envisioned by the ‎United ‎States and other participants in these negotiations.‎ As for the truce (hudna) in the Gaza Strip between Hamas and the Israeli ‎Government, all parties ‎are still satisfied with their commitment to the ‎conditions of the truce. Some evasions of ceasefire ‎occur every now and ‎then and several Palestinian factions in the Strip declared more than once ‎‎that the truce is fragile and that Israel is not committed to its terms and ‎conditions.‎